2014
DOI: 10.1002/jcp.24816
|View full text |Cite
|
Sign up to set email alerts
|

IL‐1β Promotes Malignant Transformation and Tumor Aggressiveness in Oral Cancer

Abstract: Chronic inflammation, coupled with alcohol, betel quid, and cigarette consumption, is associated with oral squamous cell carcinoma (OSCC). Interleukin-1 beta (IL-1b) is a critical mediator of chronic inflammation and implicated in many cancers. In this study, we showed that increased pro-IL-1b expression was associated with the severity of oral malignant transformation in a mouse OSCC model induced by 4-Nitroquinolin-1-oxide (4-NQO) and arecoline, two carcinogens related to tobacco and betel quid, respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
133
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(151 citation statements)
references
References 39 publications
7
133
0
1
Order By: Relevance
“…Expression datasets of human cell line were excluded in the study. The included GEO datasets (GSE) are shown in Table 1 (24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35).…”
Section: Methodsmentioning
confidence: 99%
“…Expression datasets of human cell line were excluded in the study. The included GEO datasets (GSE) are shown in Table 1 (24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35).…”
Section: Methodsmentioning
confidence: 99%
“…Secretion of IL-1b stimulates cells to produce the chemokine CXCL1 in HNSCC. 40 CXCL1 is one of the ligands of the chemokine receptor CXCR2, which is a crucial chemokine for the recruitment of MDSCs to sites of inflammation. 41 Our previous study demonstrated the high level of CXCL1 in tongue SCC as compared with normal tongue.…”
mentioning
confidence: 99%
“…The higher intensity of inflammation in lower lip SCCs compared to oral cavity neoplasms reported previously 24 and the downregulating effect of inflammation on ECad, 25 may help explain this finding.…”
Section: Discussionmentioning
confidence: 59%